Characterization and Immunogenicity of HIV Envelope gp140 Zera® Tagged Antigens - Ximba, Phindile; Chapman, Rosamund; Meyers, Ann E.; Margolin, Emmanuel; van Diepen, Michiel T.; Williamson, Anna-Lise; Rybicki, Edward P. (Frontiers in Bioengineering and Biotechnology, 2020)
HIV-1 envelope glycoprotein (Env) remains the most relevant target for the elicitation of functional antibodies to HIV by vaccination. However, soluble Env antigens often do not elicit the desired immune responses. Delivering subunit antigens on particulate nanoparticles is an established approach to improve their immunogenicity. In this study the sequence encoding Zera®, a proline-rich domain derived from the ɣ-zein storage protein, was fused to either the C- or N-terminus of the superinfecting HIV-1 CAP256 gp140 envelope: Zera® generally induces the formation of protein bodies (PBs), which can significantly improve both the immunogenicity and yields of the partner protein. The expression of gp140-Zera® and Zera®-gp140 (N- and C-terminal fusions respectively) in mammalian cells was confirmed by western blot analysis and immunostaining. However, isopycnic ultracentrifugation showed that neither gp140-Zera® nor Zera®-gp140 accumulated in characteristic electron-dense PBs. gp140-Zera® elicited higher binding antibody titres in rabbits to autologous gp140 and V1V2 scaffold than Zera®-gp140. Rabbit anti-gp140-Zera® sera also had significantly higher Tier 1A neutralising antibody titres than anti-Zera®-gp140 sera. Neither gp140-Zera® nor Zera®-gp140-specific sera neutralised Tier 1B or autologous Tier 2 viruses. These results showed that HIV-1 gp140 tagged with Zera® at either the N- or C-termini elicited high titres of gp140 and V1V2 binding antibodies, and low levels of Tier 1 neutralising antibodies in rabbits.